Local Peacebuilding in Afghanistan and the Prospects for Democracy After the U.S. Withdrawal - Azam, Maryam; Aqeel, Ayesha (Journal of Development and Social Sciences, 2025)
This study examines localized peacebuilding strategies under Taliban rule and assesses the viability of democratic governance in Afghanistan after the U.S. withdrawal. Afghanistan’s prolonged conflict is rooted in internal power struggles, socio-economic underdevelopment, and global geopolitical rivalries. The U.S.-led intervention post-2001 failed to achieve lasting peace, culminating in the Taliban’s return to power in 2021. Despite the end of formal warfare, underlying tensions and drivers of conflict remain. A qualitative approach is used, drawing on exiting literature, policy analysis, and reports to evaluate local peacebuilding under Taliban rule. The Taliban government has excluded women and minorities, suppressed political dissent, and alienated the international community. Peace efforts remain fragmented and localized, lacking formal support structures. Some communities have adopted informal conflict resolution mechanisms, but broader political reconciliation is absent. The regime’s ideological rigidity and ties to extremist groups hinder democratic development. The study identifies that international actors should support grassroots peace initiatives and civil society resilience.